Ectopic overexpression of ShCBF1 and SlCBF1 in tomato suggests an alternative view of fruit responses to chilling stress postharvest - Albornoz, Karin; Zhou, Jiaqi; Zakharov, Florence; Grove, Jonas; Wang, Minmin; Beckles, Diane M. (Frontiers in Plant Science, 2024)
Postharvest chilling injury (PCI) is a physiological disorder that often impairs tomato fruit ripening; this reduces fruit quality and shelf-life, and even accelerates spoilage at low temperatures. The CBF gene family confers cold tolerance in Arabidopsis thaliana, and constitutive overexpression of CBF in tomato increases vegetative chilling tolerance, in part by retarding growth, but, whether CBF increases PCI tolerance in fruit is unknown. We aimed to induce high levels of CBF1 cloned from S. lycopersicum and S. habrochaites in fruit undergoing postharvest chilling, using the stress-inducible RD29A promoter. We hypothesized that CBF1 overexpression (OE) would be induced in the cold and increase resistance to PCI. Harvested fruit were cold-stored (2.5°C) for up to three weeks, then rewarmed at 20°C for three days. Transgene upregulation was triggered during cold storage from 8.6to 28.6-fold in SlCBF1-OE, and between 3.1-to 8.3-fold in ShCBF1-OE fruit, but developmental abnormalities in the absence of cold induction were visible. Remarkably, transgenic fruit displayed worsening of PCI symptoms, i.e., failure to ripen after rewarming, comparatively higher susceptibility to decay relative to wild-type (WT) fruit, lower total soluble solids, and the accumulation of volatile compounds responsible for off-odors. These symptoms correlated with CBF1 overexpression levels. Transcriptomic analysis revealed that the ripening and biotic and abiotic stress responses were altered in the cold-stored transgenic fruit. Seedlings grown from 'chilled' and 'non-chilled' WT fruit, in addition to 'non-chilled' transgenic fruit were also exposed to 0°C to test their photosynthetic response to chilling injury. Chilled WT seedlings adjusted their photosynthetic rates to reduce oxidative damage; 'non-chilled' WT seedlings did not. Photosynthetic parameters between transgenic seedlings were similar at 0°C, but SlCBF1-OE showed more severe photoinhibition than ShCBF1-OE, mirroring phenotypic observations. These results suggest that 1) CBF1 overexpression accelerated fruit deterioration in response to cold storage, and 2) Chilling acclimation in fructus can increase chilling tolerance in seedling progeny of WT tomato.